Curable composition, cured product, overcoat film for flexible wiring board, flexible wiring board and method for producing flexible wiring board

A curable composition for flexible wiring boards, comprising polyurethane with specific aromatic ring concentration, epoxy groups, and an olefin-based antifoaming agent, addresses issues of wire breakage, warpage, and antifoaming, providing enhanced performance and safety without fluorine.

JP2025013236AActive Publication Date: 2025-01-24NIPPON POLYTECH CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024108276
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-13
Filing Date
2024-07-04
Publication Date
2025-01-24
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

Existing curable compositions used in protective films for flexible wiring boards lack improvements in resistance to wire breakage, warpage, flexibility, and antifoaming properties, and often contain fluorine-containing compounds that are undesirable from a safety perspective.

Method used

A curable composition comprising polyurethane with an organic residue derived from polyisocyanate containing a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol/g, a solvent, a compound with two or more epoxy groups, and an antifoaming agent containing olefin, without fluorine atoms, is developed to enhance resistance to disconnection, low warpage, and flexibility.

Benefits of technology

The composition achieves excellent resistance to wire breakage, low warpage, and antifoaming properties while being free from fluorine atoms, resulting in improved performance and safety for flexible wiring boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025013236000001
    Figure 2025013236000001
  • Figure 2025013236000002
    Figure 2025013236000002
  • Figure 2025013236000003
    Figure 2025013236000003
Patent Text Reader

Abstract

To provide a curable composition, a cured product, an overcoat film for a flexible wiring board and a flexible wiring board which have excellent disconnection suppression property, low warpage property, flexibility and defoaming properties and contain no fluorine atom and a method for producing a flexible wiring board.SOLUTION: There are provided: a curable composition, a cured product, an overcoat film for a flexible wiring board and a flexible wiring board which contain (component a) a polyurethane containing an organic residue derived from a polyisocyanate having a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol / g, (component b) a solvent, (component c) a compound having two or more epoxy groups in one molecule and (component d) a defoaming agent containing an olefin, and do not contain fluorine atom; and a method for producing a flexible wiring board.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable composition, a cured product, an overcoat film for a flexible wiring board, a flexible wiring board, and a method for producing a flexible wiring board. [Background technology]

[0002] Conventionally, the surface protection film of a flexible wiring circuit is of a type in which a polyimide film called a coverlay film is cut into a mold according to a pattern, and then attached using an adhesive, or of a type in which a flexible ultraviolet-curable or heat-curable overcoat agent is applied by screen printing, the latter being particularly useful in terms of workability. As these curable overcoat agents, resin compositions mainly made of epoxy resins, acrylic resins, or composites of these are known. These often contain, as the main component, a resin that has been modified by introducing, in particular, a butadiene skeleton, a siloxane skeleton, a polycarbonate diol skeleton, a long-chain aliphatic skeleton, or the like.

[0003] However, in recent years, flexible substrates have become lighter and thinner as electronic devices become lighter and smaller, and this has led to a stronger demand for improvements in the physical properties of the overcoating resin composition.

[0004] As a related technique, for example, Patent Document 1 discloses a curable composition that contains polyurethane, a solvent, and a compound having two or more epoxy groups in one molecule, which can be used for a protective film of a flexible wiring board.

[0005] Patent Document 2 discloses a curable polyurethane resin composition that contains a curable polyurethane resin (A) and an antifoaming agent (B) as essential components, and uses an ethylene-α-olefin co-oligomer as the antifoaming agent (B). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6912385 [Patent Document 2] Japanese Patent Application Publication No. 05-247161 Summary of the Invention [Problem to be solved by the invention]

[0007] However, there is room for further improvement in the curable composition used in the protective film. For example, further improvement is desired in the physical properties such as the suppression of disconnection, low warpage, flexibility, and defoaming property of the curable composition when the cured product is used in the protective film of wiring of flexible wiring boards, etc. In addition, from the viewpoint of safety, it is desired to avoid the use of fluorine-containing compounds such as PFAS (organic fluorine compounds) as much as possible. From this viewpoint, it is desired to develop a curable composition that does not contain fluorine atoms but can exhibit excellent physical properties.

[0008] In view of the above circumstances, the present invention aims to provide a curable composition, a cured product, an overcoat film for a flexible wiring board, a flexible wiring board, and a method for producing a flexible wiring board, which have excellent breakage prevention properties, low warpage properties, flexibility, and defoaming properties and do not contain fluorine atoms. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems and have found that a curable composition containing no fluorine atoms comprises (component a) a polyurethane having a carboxyl group and an organic residue derived from a polyisocyanate, the polyurethane having an aromatic ring concentration of 0.1 to 6.5 mmol / g, (component b) a solvent, (component c) a compound having two or more epoxy groups in one molecule, and (component d) an olefin-containing defoamer, and have thus completed the present invention.

[0010] That is, the present invention is as follows.

[0011] <1> The curable composition contains (component a) a polyurethane containing an organic residue derived from a polyisocyanate, which has a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol / g, (component b) a solvent, (component c) a compound having two or more epoxy groups in one molecule, and (component d) a first defoaming agent containing an olefin, and does not contain a fluorine atom. <2> Component a is represented by the formula (1)

[0012] [ka]

[0013] A polyurethane having a structural unit represented by the formula: <1> The curable composition according to claim 1, <3> Component a is represented by formula (2)

[0014] [ka]

[0015] (where R 1 each independently represents a phenylene group or a phenylene group having a substituent. A polyurethane having a structural unit represented by the formula: <1> or <2> The curable composition according to claim 1, <4> Component a is represented by formula (3)

[0016] [ka]

[0017] (where n R 1 each independently represents a phenylene group or a phenylene group having a substituent, (n+1) R 2 each independently represents an alkylene group having 3 to 9 carbon atoms, and n is a natural number of 50 or less. A polyurethane having a structural unit represented by the formula: <1> or <2> The curable composition according to claim 1, <5> In component a, the organic residue derived from a cyclic aliphatic polyisocyanate accounts for 70 mol % or more of the total amount of organic residues derived from the polyisocyanate. <1> or <2> The curable composition according to claim 1, <6> Component a is 60 to 99.9 mass% based on the total amount of components a and c; <1> or <2> The curable composition according to claim 1, <7> Component b is 25 to 75 mass% based on the total amount of components a, b and c; <1> or <2> The curable composition according to claim 1, <8> The number average molecular weight of component a is 3,000 to 50,000, and the acid value of component a is 10 to 70 mgKOH / g. <1> or <2> The curable composition according to claim 1, <9> (Component e) a second defoamer containing an acrylic resin and / or a methacrylic resin; <1> or <2> The curable composition according to claim 1, <10> The total amount of component d and component e is 0.01 to 3 mass%. <9> The curable composition according to claim 1, <11> the total amount of components d and e is 0.01 to 5 mass% when the total amount of components excluding the content of component b from the total amount of the curable composition is taken as 100 mass%; <9> The curable composition according to claim 1, <12> Component e is 1 to 150 mass% based on component d; <9> The curable composition according to claim 1, <13> (Component f) further comprising at least one type of fine particles selected from the group consisting of inorganic fine particles and organic fine particles; <1> or <2> The curable composition according to claim 1, <14> Component f contains silica microparticles; <13> The curable composition according to claim 1, <15> Component f contains hydrotalcite fine particles; <13> The curable composition according to claim 1, <16> <1> or <2> 2. A cured product of the curable composition according to claim 1. <17> <16> 2. An overcoat film for flexible wiring boards comprising the cured product according to claim 1. <18> A part or the whole of the surface on which the wiring is formed of a flexible wiring board formed on a flexible substrate <17> 2. A flexible wiring board covered with the overcoat film for flexible wiring board according to claim 1. <19> (Step A) A flexible wiring board having wiring formed on a flexible substrate is provided with a method for forming a flexible wiring board, comprising: <1> or <2> forming a printed film on the wiring by printing the curable composition according to the above item; (Step B) A step of evaporating a part or all of the solvent in the printed film by placing the printed film obtained in Step A in an atmosphere of 40°C to 100°C; (Step C) A method for producing a flexible wiring board covered with an overcoat film includes a step of curing the printed film obtained in step A or the printed film obtained in step B by heating at 100°C to 170°C to form an overcoat film. Effect of the Invention

[0018] According to the present invention, it is possible to provide a curable composition, a cured product, an overcoat film for a flexible wiring board, a flexible wiring board, and a method for producing a flexible wiring board, which are excellent in breakage prevention properties, low warpage properties, flexibility, and defoaming properties and do not contain fluorine atoms. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment for carrying out the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. The present embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out by appropriately modifying it within the scope of its gist.

[0020] <Curable composition>

[0021] The curable composition according to the present embodiment is a curable composition that contains (component a) a polyurethane having a carboxyl group and an organic residue derived from a polyisocyanate, with an aromatic ring concentration of 0.1 to 6.5 mmol / g, (component b) a solvent, (component c) a compound having two or more epoxy groups in one molecule, and (component d) a first defoaming agent containing an olefin, and does not contain a fluorine atom. Each component will be described below.

[0022] (Component a)

[0023] Component a is a polyurethane having a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol / g, and contains an organic residue derived from a polyisocyanate. Polyurethane is defined as a substance having a plurality of urethane bonds.

[0024] Examples of the aromatic ring structure of component a include a benzene ring structure, a biphenyl structure, a naphthalene structure, and a fluorene structure.

[0025] The aromatic ring concentration of component a is 0.1 to 6.5 mmol / g, with the lower limit being preferably 0.5 mmol / g or more, more preferably 1.6 mmol / g or more, even more preferably 2.0 mmol / g or more, and even more preferably 2.5 mmol / g or more, and the upper limit being preferably 6.3 mmol / g or less, more preferably 6.0 mmol / g or less, and even more preferably 5.8 mmol / g or less.

[0026] In addition, an example of a preferred combination of the upper and lower limits is 0.1 to 6.5 mmol (i.e., 0.1 to 6.5 mmol / g) relative to the component a1g, preferably 0.1 to 6.3 mmol (i.e., 0.1 to 6.3 mmol / g) relative to the component a1g, more preferably 0.5 to 6.3 mmol (i.e., 0.5 to 6.3 mmol / g) relative to the component a1g, even more preferably 1.6 to 6.0 mmol (i.e., 1.6 to 6.0 mmol / g) relative to the component a1g, and even more preferably 2.0 to 6.0 mmol (i.e., 2.0 to 6.0 mmol / g) relative to the component a1g. When the aromatic ring concentration of the component a is within the above-mentioned range, it becomes easy to balance the solvent resistance of the overcoat film of the present embodiment described later and the breakage suppression and warpage of the flexible wiring board of the present embodiment described later (however, the action and effect of the present embodiment are not limited thereto).

[0027] The aromatic ring concentration can be calculated from the feed ratio, 1 H-NMR, 13 After determining the structure by C-NMR and IR, 1 Comparison of the number of protons derived from aromatic rings and units in H-NMR ( 1 It can also be analyzed by comparing the integral curves of H-NMR.

[0028] In this specification, the number of aromatic rings is counted as 1 for each aromatic ring, and fused rings are also counted as 1. For example, in the case of a benzene ring as shown in formula (51), the number of aromatic rings is counted as 1. Since a biphenyl structure as shown in formula (52) and a 9H-fluorene structure as shown in formula (53) have two benzene rings, the number of aromatic rings is counted as 2. In the case of a naphthalene structure as shown in formula (54), the number of aromatic rings is counted as 2. Similarly, in the case of an anthracene structure (formula (55)) or a phenanthrene structure (formula (56)), the number of aromatic rings is counted as 3. In the case of a triphenylene structure (formula (57)) or a binaphthyl structure (formula (58)), the number of aromatic rings is counted as 4.

[0029] The number of circles in formulae (51') to (58') represents the number of aromatic rings in formulae (51) to (58), respectively.

[0030] [ka]

[0031] [ka]

[0032] [ka]

[0033] [ka]

[0034] [ka]

[0035] [ka]

[0036] [ka]

[0037] [ka]

[0038] [ka]

[0039] [ka]

[0040] [ka]

[0041] [ka]

[0042] [ka]

[0043] [ka]

[0044] [ka]

[0045] [ka]

[0046] There is no particular limitation on the method for producing component a, but for example, it can be synthesized by reacting a polyisocyanate compound, a carboxyl group-containing diol, a polyol other than the carboxyl group-containing diol, and optionally a monohydroxyl compound and a monoisocyanate compound, using a solvent in the presence or absence of a known urethane catalyst such as dibutyltin dilaurate. This reaction is preferably carried out without a catalyst, since the physical properties such as the wire breakage suppression, flexibility, and low warpage of the overcoat film of this embodiment described later are improved.

[0047] There are no particular limitations on the structure of component a, so long as it is a polyurethane containing an organic residue derived from a polyisocyanate that has a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol / g. However, it is preferable for component a to have at least one of a structural unit of formula (1) and a structural unit of formula (2), and it is more preferable for component a to have both.

[0048] [ka]

[0049] [ka]

[0050] (where R 1 each independently represents a phenylene group or a phenylene group having a substituent.

[0051] Furthermore, it is preferable that component a is a polyurethane having a structural unit represented by formula (3). More specifically, it is more preferable that a part or all of the structural unit of formula (2) is present in the polyurethane as a part of the structural unit represented by formula (3).

[0052] [ka]

[0053] (where n R 1 each independently represents a phenylene group or a phenylene group having a substituent, (n+1) R 2 each independently represents an alkylene group having 3 to 9 carbon atoms, and n is a natural number of 50 or less.

[0054] In addition, R in formula (2) and formula (3) 1each independently represents a phenylene group or a phenylene group having a substituent, and is preferably a phenylene group. Examples of the substituent include an alkyl group having 1 to 5 carbon atoms and a halogen atom. However, from the viewpoint of being fluorine-free, particularly halogen-free, the substituent is preferably not a fluorine atom, and more preferably not a halogen atom.

[0055] R 2 each independently represents an alkylene group having 3 to 9 carbon atoms, 2 Preferably, it has 3 to 8 carbon atoms, and more preferably 4 to 8 carbon atoms.

[0056] An example of a compound having the structural unit of formula (1) is 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene shown in formula (4).

[0057] [ka]

[0058] Examples of compounds having a structural unit of formula (3) include polyester polyols consisting of a combination of at least one selected from the group of dicarboxylic acids below and at least one selected from the group of diols below.

[0059] Examples of dicarboxylic acids include phthalic acid, isophthalic acid, terephthalic acid, 3-methyl-benzene-1,2-dicarboxylic acid, 4-methyl-benzene-1,2-dicarboxylic acid, 4-methyl-benzene-1,3-dicarboxylic acid, 5-methyl-benzene-1,3-dicarboxylic acid, and 2-methyl-benzene-1,4-dicarboxylic acid. Only one of these can be used, or two or more can be used.

[0060] Examples of diols include 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,8-octanediol, 1,9-nonanediol, 2,4-diethyl-1,5-pentanediol, and 2-ethyl-2-butyl-1,3-propanediol. Only one of these can be used, or two or more can be used.

[0061] Preferred dicarboxylic acids include phthalic acid, isophthalic acid, terephthalic acid, 3-methyl-benzene-1,2-dicarboxylic acid, and 4-methyl-benzene-1,2-dicarboxylic acid, and more preferably phthalic acid.

[0062] As the diol, preferred examples include 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 3-methyl-1,5-pentanediol, and more preferred are 1,6-hexanediol and 3-methyl-1,5-pentanediol.

[0063] As the polyester polyol having a structural unit of the formula (3), it is preferable to use one having a number average molecular weight of 800 to 5,000, more preferably 800 to 4,000, and even more preferably 900 to 3,500.

[0064] As the polyester polyol having the structural unit of formula (3), one type of polyester polyol may be used, or two or more types may be used in combination.

[0065] The carboxyl group-containing diol used as the raw material of component a is not particularly limited as long as it is a compound having one or more carboxyl groups and two alcoholic hydroxyl groups in the molecule. Specific examples of the carboxyl group-containing diol include dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, and N,N-bis(hydroxyethyl)glycine. Among these, dimethylolpropionic acid and 2,2-dimethylolbutanoic acid are preferred from the viewpoint of solubility in the synthesis reaction solvent of component a. These carboxyl group-containing diols may be used alone or in combination of two or more.

[0066] When a low molecular weight polyol is used as a polyol other than the polyester polyol having the structural unit of formula (3) and the carboxyl group-containing diol, for example, 1,2-propanediol, 1,3-butanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, diethylene glycol, dipropylene glycol, glycerin, trimethylolpropane, etc. can be used alone or in combination of two or more, and it is preferable to use 1,6-hexanediol or 3-methyl-1,5-pentanediol.

[0067] The polyisocyanate compound used in the synthesis of component a is not particularly limited as long as it is a compound having two or more isocyanato groups. Specific examples of the polyisocyanate compound include cycloaliphatic polyisocyanates such as 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, norbornane diisocyanate, and biuret of isophorone diisocyanate; 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, diphenylmethane-4,4'-diisocyanate, 1,3 Examples of the polyisocyanates include polyisocyanates having an aromatic ring such as xylylene diisocyanate and 1,4-xylylene diisocyanate; chain aliphatic polyisocyanates such as biuret of hexamethylene diisocyanate, lysine triisocyanate, lysine diisocyanate, hexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, and 2,2,4-trimethylhexanemethylene diisocyanate; and polyisocyanates having a heterocyclic ring such as isocyanurate of isophorone diisocyanate and isocyanurate of hexamethylene diisocyanate. These may be used alone or in combination of two or more.

[0068] Among these, in order to maintain high heat resistance and electrical insulation performance of the cured product according to the present embodiment described below, it is preferable that the cyclic aliphatic polyisocyanate is contained in an amount of 70 mol % or more relative to the total amount of isocyanates (i.e., in component a, the organic residues derived from the cyclic aliphatic polyisocyanate are 70 mol % or more relative to the total amount of organic residues derived from the polyisocyanate), more preferably 80 mol % or more, and even more preferably 90 mol % or more.

[0069] Among these cyclic aliphatic polyisocyanates, preferred are isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane and norbornane diisocyanate, more preferred are methylene bis(4-cyclohexyl isocyanate), isophorone diisocyanate and norbornane diisocyanate, and even more preferred is methylene bis(4-cyclohexyl isocyanate).

[0070] The monohydroxyl compound used as the raw material of component a as required is not particularly limited as long as it has one alcoholic hydroxyl group in the molecule and does not have any other substituent that is more reactive with isocyanato group than alcoholic hydroxyl group.Specific examples of the monohydroxyl compound include methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, t-butanol, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monoisobutyl ether, dipropylene glycol monopropyl ether, methyl ethyl ketoxime, etc.

[0071] These monohydroxyl compounds may be used alone or in combination of two or more.

[0072] As a raw material of component a, the monoisocyanate compound used as required can be cyclohexyl isocyanate, octadecyl isocyanate, phenyl isocyanate, toluyl isocyanate, etc. Considering the discoloration resistance of the curable composition according to this embodiment when heated, cyclohexyl isocyanate and octadecyl isocyanate are preferred.

[0073] In order to maintain high electrical insulation performance and high heat resistance of the cured product according to the present embodiment described later, it is preferable that the raw material polyol contains an aromatic ring, and it is more preferable that only the raw material polyol contains an aromatic ring and the raw material polyisocyanate does not contain an aromatic ring (i.e., polyisocyanate having an aromatic ring is not used as a raw material). In the method for producing component a, the blending amounts of each component are as follows.

[0074] When a compound having a structural unit of formula (1) is used, the amount of the compound having the structural unit of formula (1) used relative to the total amount of the raw materials of component a is preferably 3 to 20 mass%, more preferably 5 to 15 mass%. When the amount of the compound having the structural unit of formula (1) used relative to the total amount of the raw materials of component a is 3 to 20 mass%, a balance can be achieved between the low warpage property and the effect of suppressing disconnection of the flexible wiring board covered with the overcoat film of this embodiment described later.

[0075] When a polyester polyol having a structural unit of formula (3) is used, the amount of the polyester polyol having the structural unit of formula (3) used relative to the total amount of the raw materials of component a is preferably 30 to 70 mass%, more preferably 35 to 70 mass%, and even more preferably 40 to 70 mass%. When the amount of the polyester polyol having the structural unit of formula (3) used relative to the total amount of the raw materials of component a is 30 to 70 mass%, the elastic modulus of the overcoat film described below is not too low, and the cured film is not too brittle, so that a well-balanced overcoat film can be obtained.

[0076] The solid content concentration during production of component a is preferably 10 to 90 mass%, more preferably 15 to 70 mass%, and even more preferably 20 to 60 mass%. When a solution having a solid content concentration of 20 to 60 mass% is used to produce a curable composition according to the present embodiment described below, the solution viscosity of component a solution is preferably, for example, 5000 to 1,000,000 mPa s under the measurement conditions described in the Examples from the viewpoint of uniform dispersion.

[0077] There is no particular restriction on the order of charging the raw materials into a reactor when producing component a, but for example, the compound of formula (4), the polyester polyol having the structural unit of formula (3), the carboxyl group-containing diol, and, if necessary, the compound of formula (4), the polyol having the structure of formula (3), and the polyol other than the carboxyl group-containing diol are charged into a reactor first and dissolved in a solvent. Then, a polyisocyanate compound is added dropwise usually at 20°C to 140°C, more preferably 60°C to 120°C, and then the above components are reacted at 50°C to 160°C, more preferably 60°C to 150°C.

[0078] The molar ratio of the raw materials is adjusted according to the molecular weight and acid value of the desired component a. The molecular weight of the desired component a can also be adjusted by using a monohydroxyl compound. That is, when the desired number average molecular weight is reached (or when it approaches the desired number average molecular weight), a monohydroxyl compound can be added to block the terminal isocyanato group and suppress further increase in the number average molecular weight.

[0079] When a monohydroxyl compound is used, there is no problem whether the number of isocyanato groups of the polyisocyanate compound is less than, the same as, or more than the total number of hydroxyl groups of the raw materials of component a, which is the combination of the compound of formula (4), the polyester polyol having a structural unit of formula (3), and the polyol components other than the compound of formula (4) and the polyol having the structure of formula (3).

[0080] Furthermore, when an excessive amount of the monohydroxyl compound is used, unreacted monohydroxyl compound will remain. In this case, the excess monohydroxyl compound may be used as it is as part of the solvent, or may be removed by distillation or the like.

[0081] In addition, in order to use a monoisocyanate compound as a raw material for component a, it is necessary to make the number obtained by subtracting the number of isocyanate groups of the monoisocyanate compound from the number of isocyanate groups of all raw materials of component a (i.e., the total number of isocyanate groups of the polyisocyanate compound used as a raw material for component a) smaller than the total number of alcoholic hydroxyl groups of all raw materials of component a so that the terminal of the polyurethane being produced before using the monoisocyanate compound in the reaction becomes a hydroxyl group. At the time when the reaction between the alcoholic hydroxyl groups of all raw materials of component a and the isocyanate groups of the polyisocyanate compound used in component a is almost completed, in order to react the hydroxyl groups remaining at the terminal of the polyurethane being produced with the monoisocyanate compound, the monoisocyanate compound is dropped into the solution of the carboxyl group-containing polyurethane being produced at 30°C to 150°C, more preferably 70°C to 140°C, and then maintained at the same temperature to complete the reaction.

[0082] The number average molecular weight of the component a obtained as described above is preferably 3,000 to 50,000, more preferably 5,000 to 50,000, and even more preferably 5,000 to 30,000. When the number average molecular weight is within the above range, the breakage suppression, flexibility, and low warpage of the cured film can be further improved. Furthermore, the flexibility, elongation, and strength are not impaired, the solubility of the component a in a solvent (i.e., component b) is good, and the viscosity does not become too high even when dissolved, so that the physical properties can be further improved. This makes the curable composition according to this embodiment suitable for use in the manufacture of a flexible wiring board covered with the overcoat film for flexible wiring boards of this embodiment described below.

[0083] The term "number average molecular weight" as used herein refers to a polystyrene-equivalent number average molecular weight measured by gel permeation chromatography (hereinafter, referred to as GPC). In this specification, unless otherwise specified, the measurement conditions for GPC are as follows. Device name: JASCO Corporation HPLC unit HSS-2000 Column: Shodex column LF-804 Mobile phase: Tetrahydrofuran Flow rate: 1.0mL / min Detector: JASCO RI-2031Plus Temperature: 40.0℃ Sample volume: Sample loop 100μL Sample concentration: adjusted to around 0.1% by mass.

[0084] The acid value of component a is preferably 10 to 70 mgKOH / g, more preferably 15 to 50 mgKOH / g. When the acid value is 10 to 70 mgKOH / g, the reactivity with other components contained in the curable composition according to this embodiment, such as a compound having two or more epoxy groups in one molecule (i.e., component c) described later, is not reduced, and the heat resistance of the cured product of this embodiment described later is not reduced, and the product does not become too hard and brittle. In addition, it is easy to balance the solvent resistance of the overcoat film described later and the warpage of the flexible wiring board of this embodiment described later. In this specification, the acid value of component a is the acid value measured by potentiometric titration according to JIS K0070.

[0085] The content of component a is preferably 60 to 99.9 mass% (a / (a+c)) relative to the total amount of components a and c. The lower limit of this content (a / (a+c)) is more preferably 70 mass% or more, even more preferably 80 mass% or more, even more preferably 90 mass% or more, and even more preferably 93 mass% or more. The upper limit of this content (a / (a+c)) is more preferably 99.5 mass% or less, even more preferably 99.3 mass% or less, and even more preferably 99.0 mass% or less.

[0086] (component b)

[0087] The solvent (component b), which is one of the essential components of the curable composition according to this embodiment, is not particularly limited as long as it can dissolve component a, but preferably has a boiling point of 150°C or more and 250°C or less under atmospheric pressure. In terms of balancing the solubility of component a and the volatility of the solvent, it is possible and preferable to use two or more solvents having a boiling point of 150°C or more and 250°C or less under atmospheric pressure. More preferably, a solvent having a boiling point of 170°C or more and less than 200°C under atmospheric pressure and a solvent having a boiling point of 200°C or more and 220°C or less under atmospheric pressure are used in combination.

[0088] Examples of solvents having a boiling point of 170°C or higher and lower than 200°C under atmospheric pressure include diethylene glycol diethyl ether (boiling point 189°C), diethylene glycol ethyl methyl ether (boiling point 176°C), dipropylene glycol dimethyl ether (boiling point 171°C), 3-methoxybutyl acetate (boiling point 171°C), and ethylene glycol monobutyl ether acetate (boiling point 192°C).

[0089] Examples of solvents having a boiling point of 200°C or higher and 220°C or lower under atmospheric pressure include diethylene glycol butyl methyl ether (boiling point 212°C), tripropylene glycol dimethyl ether (boiling point 215°C), triethylene glycol dimethyl ether (boiling point 216°C), ethylene glycol dibutyl ether (boiling point 203°C), diethylene glycol monoethyl ether acetate (boiling point 217°C), diethylene glycol monoethyl ether acetate (boiling point 217°C), and γ-butyrolactone (boiling point 204°C).

[0090] Since the high volatility of the solvents makes it possible to impart low-temperature curing properties and the production reaction of component a can be efficiently carried out in a homogeneous system, it is preferable to combine at least one solvent selected from the group consisting of diethylene glycol diethyl ether (boiling point 189°C), diethylene glycol ethyl methyl ether (boiling point 176°C), and dipropylene glycol dimethyl ether (boiling point 171°C) as a solvent having a boiling point of 170°C or more and less than 200°C under atmospheric pressure with at least one solvent selected from the group consisting of diethylene glycol monoethyl ether acetate (boiling point 217°C) and γ-butyrolactone (boiling point 204°C) as a solvent having a boiling point of 200°C or more and 220°C or less under atmospheric pressure. More preferably, diethylene glycol diethyl ether (boiling point 189°C) is combined as a solvent having a boiling point of 170°C or more and less than 200°C at atmospheric pressure, and diethylene glycol monoethyl ether acetate (boiling point 217°C) and γ-butyrolactone (boiling point 204°C) are combined as solvents having a boiling point of 200°C or more and 220°C or less at atmospheric pressure.

[0091] These preferred solvent combinations have low hygroscopicity, high boiling points and low volatility, making them excellent solvents for screen printing inks.

[0092] In order to fully exert the above-mentioned effects, the ratio by mass of the solvent having a boiling point of 170°C or more and less than 200°C under atmospheric pressure to the solvent having a boiling point of 200°C or more and 220°C or less under atmospheric pressure is preferably in the range of 5:95 to 80:20, and more preferably in the range of 10:90 to 60:40.

[0093] As part of these preferred solvents, the solvent used in synthesis when producing the above-mentioned component a can be used as it is as part of the solvent for the curable composition according to this embodiment, and this is preferable in terms of process.

[0094] In addition, to the extent that the solubility of component a is not impaired, a solvent other than the solvent having a boiling point of 170° C. or more and less than 200° C. under atmospheric pressure and the solvent having a boiling point of 200° C. or more and 220° C. or less under atmospheric pressure can be used in combination. Reactive monomers and reactive diluents can also be used as solvents.

[0095] The content of component b in the curable composition according to this embodiment is preferably 25 to 75% by mass, more preferably 35 to 70% by mass, and even more preferably 35 to 65% by mass, based on the total amount of components a, b, c, and f (total amount of components a, b, and c) of the curable composition according to this embodiment (however, when component f is not included in the curable composition according to this embodiment, the total amount of components a, b, and c). When the content of component b is in the range of 25 to 75% by mass based on the total amount of components a, b, c, and f (total amount of components a, b, and c) of the curable composition according to this embodiment (however, when component f is not included in the curable composition according to this embodiment, the total amount of components a, b, and c) of the curable composition according to this embodiment, the viscosity of the curable composition is good for printing by the screen printing method, and the spread due to bleeding of the curable composition after screen printing is not so large. As a result, the actual printing area of ​​the curable composition is not too large compared to the area to which the curable composition is to be applied (i.e., the shape of the printing plate), which is preferable.

[0096] (component c)

[0097] Component c, which is an essential component of the curable composition according to this embodiment, is not particularly limited as long as it is a compound having two or more epoxy groups in one molecule, and functions as a curing agent in the curable composition according to this embodiment.

[0098] Examples of compounds having two or more epoxy groups in one molecule include phenol novolac epoxy resins, orthocresol novolac epoxy resins, and other novolac resins obtained by condensing or co-condensing phenols such as phenol, cresol, xylenol, resorcin, and catechol, and / or naphthols such as α-naphthol, β-naphthol, and dihydroxynaphthalene with compounds having aldehyde groups such as formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, and salicylaldehyde under an acidic catalyst. novolac-type epoxy resins in which the active hydrogen bonded to the nitrogen atom of aminophenols such as p-aminophenol and the active hydrogen bonded to the nitrogen atom of aminophenols such as p-aminophenol are replaced with a glycidyl group; diglycidyl ethers of bisphenol A, bisphenol F, bisphenol S, alkyl-substituted or unsubstituted biphenols, stilbene-based phenols, etc. (bisphenol A-type epoxy compounds, bisphenol F-type epoxy compounds, bisphenol S-type epoxy compounds, biphenyl-type epoxy compounds, stilbene-type epoxy compounds); glycidyl ethers of alcohols such as butanediol, polyethylene glycol, polypropylene glycol, etc.; glycidyl ester-type epoxy resins of carboxylic acids such as phthalic acid, isophthalic acid, tetrahydrophthalic acid, etc.; glycidyl-type or methylglycidyl-type epoxy resins such as compounds in which the active hydrogen bonded to the nitrogen atom of aminophenols such as p-aminophenol and the active hydrogen of phenolic hydroxyl groups are replaced with a glycidyl group; vinylcyclohexene diepoxide obtained by epoxidizing an olefin bond in the molecule, 3,4-epoxide, etc. alicyclic epoxy resins such as 2-(3,4-epoxy)cyclohexylmethyl-3,4-epoxycyclohexanecarboxylate and 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane; glycidyl ethers of paraxylylene and / or metaxylylene modified phenolic resins; glycidyl ethers of terpene modified phenolic resins; glycidyl ethers of dicyclopentadiene modified phenolic resins; glycidyl ethers of cyclopentadiene modified phenolic resins; glycidyl ethers of polycyclic aromatic ring modified phenolic resins;Glycidyl ethers of naphthalene ring-containing phenolic resins;Halogenated phenol novolac type epoxy resins;Hydroquinone type epoxy resins;Trimethylolpropane type epoxy resins;Linear aliphatic epoxy resins obtained by oxidizing olefin bonds with peracids such as peracetic acid;Diphenylmethane type epoxy resins;Epoxidized products of aralkyl type phenolic resins such as phenol aralkyl resins and naphthol aralkyl resins;Sulfur atom-containing epoxy resins;Tricyclo[5.2.1.0; 2,6 ]diglycidyl ether of decanedimethanol; and epoxy resins having an adamantane structure such as 1,3-bis(1-adamantyl)-4,6-bis(glycidyl)benzene, 1-[2',4'-bis(glycidyl)phenyl]adamantane, 1,3-bis(4'-glycidylphenyl)adamantane, and 1,3-bis[2',4'-bis(glycidyl)phenyl]adamantane. However, from the viewpoint of being fluorine-free, particularly halogen-free, it is preferable that component c does not contain fluorine atoms, and it is more preferable that it does not contain halogen atoms.

[0099] Among these, compounds having two or more epoxy groups in one molecule and an aromatic ring structure and / or an alicyclic structure are preferred.

[0100] From the viewpoint of further improving the physical properties of the cured product of the present embodiment described later, among the compounds having two or more epoxy groups in one molecule and an aromatic ring structure and / or an alicyclic structure, a glycidyl ether of a dicyclopentadiene-modified phenolic resin (i.e., tricyclo[5.2.1.0 2,6 ]decane structure and an aromatic ring structure and having two or more epoxy groups), epoxy resins having an adamantane structure such as 1,3-bis(1-adamantyl)-4,6-bis(glycidyl)benzene, 1-[2',4'-bis(glycidyl)phenyl]adamantane, 1,3-bis(4'-glycidyl)phenyl)adamantane and 1,3-bis[2',4'-bis(glycidyl)phenyl]adamantane (i.e., tricyclo[3.3.1.1 3,7Compounds having a tricyclodecane structure and an aromatic ring structure and having two or more epoxy groups, such as a compound having a tricyclodecane structure and an aromatic ring structure and having two or more epoxy groups, are preferred because they can provide a cured product with low water absorption, and a compound represented by the following formula (5) is more preferred.

[0101] [ka]

[0102] (In the formula, l represents a natural number.)

[0103] Furthermore, when emphasis is placed on reactivity with component a, among the compounds having two or more epoxy groups in one molecule and having an aromatic ring structure and / or an alicyclic structure, preferred are compounds having an amino group and an aromatic ring structure and two or more epoxy groups, such as glycidyl-type or methylglycidyl-type epoxy resins, such as compounds in which the active hydrogen bonded to the nitrogen atom of aniline or bis(4-aminophenyl)methane is substituted with a glycidyl group, and glycidyl-type or methylglycidyl-type epoxy resins, such as compounds in which the active hydrogen bonded to the nitrogen atom of aminophenols, such as p-aminophenol, and the active hydrogen of a phenolic hydroxyl group are substituted with a glycidyl group, and more preferred are compounds of the following formula (6).

[0104] [ka]

[0105] The component c may be used alone or in combination of two or more kinds.

[0106] The amount of component c to be blended relative to 100 parts by mass of component a, which is an essential component of the curable composition according to this embodiment, cannot be generalized because it differs depending on the amount of functional groups in component a that are reactive with carboxyl-containing epoxy groups.

[0107] However, the ratio of the number of functional groups capable of reacting with epoxy groups containing carboxyl groups contained in component a to the number of epoxy groups in component c (a compound having two or more epoxy groups in one molecule) (functional groups capable of reacting with epoxy groups / epoxy groups) is preferably in the range of 1 / 3 to 2 / 1, more preferably in the range of 1 / 2.5 to 1.5 / 1. When this ratio is in the range of 1 / 3 to 2 / 1, when the curable composition according to this embodiment is cured, there is no significant amount of unreacted component c remaining, and no significant amount of functional groups capable of reacting with epoxy groups containing carboxyl groups remaining, so that the functional groups capable of reacting with epoxy groups containing carboxyl groups and the epoxy groups in component c (a compound having two or more epoxy groups in one molecule) can react in a well-balanced manner.

[0108] The amount of component c in the curable composition according to the present embodiment is preferably 1 to 60 mass %, more preferably 2 to 50 mass %, and even more preferably 3 to 40 mass %, based on the total amount of components a and c in the curable composition. When the amount of component c in the curable composition according to the present embodiment is in the range of 1 to 60 mass %, based on the total amount of components a and c in the curable composition, a balance can be achieved between the solvent resistance of the overcoat film of the present embodiment described below and the low warpage and breakage suppression effect of the flexible wiring board characterized by being covered with the overcoat film.

[0109] (ingredient d)

[0110] Component d is a first defoaming agent containing an olefin. In this specification, the term "olefin" includes alkenes, alkene polymers, and chemically modified compounds thereof, and the term "olefin-based" includes olefins themselves and mixtures containing olefins as components. The term "alkene polymer" includes homopolymers and copolymers. Specific examples of component d include defoaming agents containing olefin polymers (e.g., olefin oligomers, olefin polymers, etc.). Component d can be a so-called olefin-based defoaming agent, and commercially available products can also be used. Specific examples of such defoaming agents include BYK-1791 (manufactured by BYK Japan Co., Ltd.), FLOWLEN AC-2000HF (manufactured by Kyoeisha Chemical Co., Ltd.), FLOWLEN AC-2200HF (manufactured by Kyoeisha Chemical Co., Ltd.), Disparlon P-465 (manufactured by Kusumoto Chemical Co., Ltd.), and Disparlon P-466 (manufactured by Kusumoto Chemical Co., Ltd.).

[0111] When the curable composition according to this embodiment is used as a resist ink composition for insulating protection of wiring (i.e., an overcoat agent for wiring boards), it is possible and preferable to use an antifoaming agent for the purposes of eliminating bubbles during printing (defoaming), suppressing the generation of bubbles (foam suppression), and removing bubbles from the liquid (defoaming).

[0112] In the curable composition according to the present embodiment, by blending at least component d as an antifoaming agent with the composition of components a, b, and c described above, it is unexpectedly possible to obtain a cured product with superior physical properties compared to antifoaming agents containing fluorine-based compounds or the like, and to maintain antifoaming effects such as antifoaming, foam suppression, and defoaming.

[0113] (ingredient e)

[0114] The curable composition according to this embodiment may and preferably contains the following component e. In the curable composition according to this embodiment, the above-mentioned effects can be expected to be further improved by using component e in addition to component d as an antifoaming agent in the composition of components a, b, and c described above.

[0115] Component e is a second defoaming agent containing an acrylic resin and / or a methacrylic resin. The acrylic resin here means a resin having an acrylic skeleton, and the methacrylic resin means a resin having a methacrylic skeleton. Component e can be a so-called acrylic defoaming agent or a methacrylic defoaming agent, and a commercially available product can also be used. Specific examples of such antifoaming agents include acrylic polymer-based antifoaming agents such as Dappo SN-348 (manufactured by San Nopco Ltd.), Dappo SN-354 (manufactured by San Nopco Ltd.), Dappo SN-368 (manufactured by San Nopco Ltd.), Disparlon 230HF (manufactured by Kusumoto Chemical Co., Ltd.), BYK-361 (manufactured by BYK Japan Co., Ltd.), BYK-381 (manufactured by BYK Japan Co., Ltd.), BYK-394 (manufactured by BYK Japan Co., Ltd.), Polyflow 36 (manufactured by Kyoeisha Chemical Co., Ltd.), Polyflow 75 (manufactured by Kyoeisha Chemical Co., Ltd.), and Polyflow 77 (manufactured by Kyoeisha Chemical Co., Ltd.). Note that the curable composition according to this embodiment can achieve a practical level of effect as an antifoaming agent even with only component e. In addition, the curable composition according to this embodiment can also improve its effect to a higher level by using component e and component d in combination as an antifoaming agent. Furthermore, in the curable composition according to this embodiment, even if only the component e and the component d are used as the defoaming agent, a sufficiently excellent effect can be obtained.

[0116] (Other defoamers)

[0117] The curable composition according to the present embodiment can sufficiently obtain the desired effect even if it does not contain any defoaming agent other than the above-mentioned components d and e, but if necessary, it may contain a defoaming agent (third defoaming agent) other than the components d and e. Specific examples of such a third defoaming agent include silicone-based defoaming agents such as BYK-333 (manufactured by BYK Japan Co., Ltd.), BYK-342 (manufactured by BYK Japan Co., Ltd.), SN DEFOAMER 470 (manufactured by San Nopco Ltd.), TSA750S (manufactured by Momentive Performance Materials Co., Ltd.), and silicone oil SH-203 (manufactured by DuPont Toray Specialty Materials Co., Ltd.), and acetylene diol-based defoaming agents such as Surfynol DF-110D (manufactured by Nissin Chemical Industry Co., Ltd.) and Surfynol DF-37 (manufactured by Nissin Chemical Industry Co., Ltd.). However, from the viewpoint of making the curable composition free of fluorine atoms, it is preferable that the curable composition according to the present embodiment does not contain a fluorine-containing silicone-based defoaming agent. From the viewpoint of being silicone-free, the curable composition according to the present embodiment preferably does not contain a defoaming agent that contains a silicone-based component such as silicone (a silicone-based defoaming agent).

[0118] Regarding the content of the defoaming agent, the total amount (d+e) of components d and e in the curable composition according to this embodiment is preferably 0.01 to 3 mass%. The lower limit of this content is more preferably 0.1 mass% or more, even more preferably 0.3 mass% or more, even more preferably 0.5 mass% or more, and even more preferably 0.6 mass% or more. The upper limit of this content is more preferably 2.5 mass% or less, even more preferably 2.0 mass% or less, even more preferably 1.5 mass% or less, and even more preferably 1.3 mass% or less.

[0119] Regarding the content of the defoaming agent, when the total amount of the components excluding the content of component b from the total amount of the curable composition according to the present embodiment is taken as 100 mass%, the total amount of components d and e is preferably 0.01 to 5 mass%. The lower limit is more preferably 0.5 mass% or more, even more preferably 1 mass% or more, still more preferably 1.5 mass% or more, even more preferably 1.7 mass% or more, and even more preferably 2 mass% or more. The upper limit is more preferably 4 mass% or less, even more preferably 3.5 mass% or less, and even more preferably 3 mass% or less.

[0120] The content of the antifoaming agent is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 4 parts by mass, and even more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the total amount of components a, b, c, and f.

[0121] The content of component e relative to component d (e / d) is preferably 1 to 150% by mass. The lower limit is more preferably 3% by mass or more, even more preferably 5% by mass or more, and even more preferably 7% by mass or more. The upper limit is more preferably 120% by mass or less, even more preferably 100% by mass or less, even more preferably 60% by mass or less, even more preferably 30% by mass or less, even more preferably 17% by mass or less, even more preferably 15% by mass or less, and even more preferably 13% by mass or less. By setting the blending ratio of component d to component e to the above mass ratio, the balance between breakage prevention, low warpage, flexibility, and defoaming properties can be improved to a higher level.

[0122] (Component f)

[0123] The curable composition according to this embodiment can and preferably contains the following component f.

[0124] Component f is at least one type of fine particles selected from the group consisting of inorganic fine particles and organic fine particles.

[0125] Examples of inorganic fine particles include silica (SiO2), alumina (Al2O3), titania (TiO2), tantalum oxide (Ta2O5), zirconia (ZrO2), silicon nitride (Si3N4), barium titanate (BaO·TiO2), barium carbonate (BaCO3), lead titanate (PbO·TiO2), lead zirconate titanate (PZT), lead lanthanum zirconate titanate (PLZT), gallium oxide (Ga2O3), spinel (MgO·Al2O3), mullite (3Al2O3·2SiO2), cordierite (CuO2), and tetrafluoroethylene (TEF). Examples of suitable materials include bentonite (2MgO·2Al2O3·5SiO2), talc (3MgO·4SiO2·H2O), aluminum titanate (TiO2-Al2O3), yttria-containing zirconia (Y2O3-ZrO2), barium silicate (BaO·8SiO2), boron nitride (BN), calcium carbonate (CaCO3), calcium sulfate (CaSO4), zinc oxide (ZnO), magnesium titanate (MgO·TiO2), barium sulfate (BaSO4), organic bentonite, carbon (C), and hydrotalcite.

[0126] The organic fine particles are preferably fine particles of a heat-resistant resin having an amide bond, an imide bond, an ester bond or an ether bond. From the viewpoint of heat resistance and mechanical properties, these resins are preferably polyimide resins or precursors thereof, polyamideimide resins or precursors thereof, or polyamide resins.

[0127] As the component f, the above-mentioned components may be used alone or in combination of two or more.

[0128] Among these, it is preferable that component f contains at least one selected from silica fine particles and hydrotalcite fine particles. That is, it is preferable that component f contains silica fine particles. Also, it is preferable that component f contains hydrotalcite fine particles. Component f may contain both silica fine particles and hydrotalcite.

[0129] The silica fine particles used in the curable composition according to the present embodiment are defined as including fine particles that are physically coated in powder form or chemically surface-treated with organic compounds. The silica fine particles used in the curable composition according to the present embodiment are not particularly limited as long as they are dispersed in the curable composition according to the present embodiment to form a paste, and for example, Aerosil provided by Nippon Aerosil Co., Ltd. can be mentioned. These silica fine particles represented by Aerosil can also be used to impart printability during screen printing, and in that case, they are used for the purpose of imparting thixotropy.

[0130] The hydrotalcite fine particles used in the curable composition according to this embodiment are Mg6A12(OH) 16 Hydrotalcite is a type of naturally occurring clay mineral, typically CO3·4H2O, and is a layered inorganic compound. (1-x) Al x (OH)2(CO3) x / 2 Hydrotalcite is a Mg / Al-based layered compound, and chloride ions (Cl 2 ) are produced by ion exchange with the carbonate groups between the layers. - ) and / or sulfate ions (SO4 - ) anion can be immobilized. Using this function, chloride ions (Cl - ) and sulfate ions (SO4 - ) and improve insulation reliability.

[0131] Examples of commercially available hydrotalcite products include STABIACE HT-1, STABIACE HT-7, and STABIACE HT-P manufactured by Sakai Chemical Industry Co., Ltd., and DHT-4A, DHT-4A-2, and DHT-4C manufactured by Kyowa Chemical Industry Co., Ltd.

[0132] The average particle size of these inorganic fine particles and / or organic fine particles is preferably 0.01 to 10 μm, more preferably 0.1 to 5 μm.

[0133] The blending amount of component f is preferably 0.1 to 60 mass%, more preferably 0.3 to 55 mass%, and even more preferably 0.5 to 40 mass%, based on the total amount of components a, b, c, and f. When the blending amount of component f is in the range of 0.1 to 60 mass%, based on the total amount of components a, b, c, and f, the viscosity of the curable composition is favorable for printing by a screen printing method, and the spread of the curable composition due to bleeding after screen printing is not so large. As a result, the actual printing area of ​​the curable composition is not too large compared to the area where the curable composition is to be applied (i.e., the shape of the printing plate), which is preferable.

[0134] (Cure accelerator)

[0135] The curable composition according to the present embodiment may further contain a curing accelerator, and is preferable. The curing accelerator is not particularly limited as long as it is a compound that accelerates the reaction between the epoxy group of component c and the carboxyl group of component a. Examples of the curing accelerator include triazine compounds such as melamine, acetoguanamine, benzoguanamine, 2,4-diamino-6-methacryloyloxyethyl-s-triazine, 2,4-methacryloyloxyethyl-s-triazine, 2,4-diamino-6-vinyl-s-triazine, and 2,4-diamino-6-vinyl-s-triazine-isocyanuric acid adduct, imidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, and 2-phenylimidazole. , 2-Undecylimidazole, 2-Heptadecylimidazole, 1-Benzyl-2-methylimidazole, 2-Phenyl-4-methylimidazole, 1-Cyanoethyl-2-methylimidazole, 1-Cyanoethyl-2-ethyl-4-methylimidazole, 1-Aminoethyl-2-ethyl-4-methylimidazole, 1-Aminoethyl-2-methylimidazole, 1-(Cyanoethylaminoethyl)-2-methylimidazole, N-[2-(2-Methyl-1-imidazolyl )ethyl]urea, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-methylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 1-cyanoethyl-2-ethyl-4-methylimidazolium trimellitate, 1-cyanoethyl-2-undecylimidazolium trimellitate, 2,4-diamino-6-[2′-methylimidazolyl-(1′)]-ethyl-s-triazine, 2,4-diamino-6-[2′ -undecylimidazolyl-(1′)]-ethyl-s-triazine, 2,4-diamino-6-[2′-ethyl-4′-methylimidazolyl-(1′)]-ethyl-s-triazine, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, N,N′-bis(2-methyl-1-imidazolylethyl)urea, N,N′-bis(2-methyl-1-imidazolylethyl)adipamide, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-phenyl-4,5-Dihydroxymethylimidazole, 2-Methylimidazole·isocyanuric acid adduct, 2-Phenylimidazole·isocyanuric acid adduct, 2,4-Diamino-6-[2′-methylimidazolyl-(1′)]-ethyl-s-triazine·isocyanuric acid adduct, 2-Methyl-4-formylimidazole, 2-Ethyl-4-methyl-5-formylimidazole, 2-Phenyl-4-methylformylimidazole, 1-Benzyl-2-phenylimidazole, 1,2-Dimethylimidazole, Imidazole compounds such as 1-(2-hydroxyethyl)imidazole, vinylimidazole, 1-methylimidazole, 1-allylimidazole, 2-ethylimidazole, 2-butylimidazole, 2-butyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-benzyl-2-phenylimidazole hydrobromide, and 1-dodecyl-2-methyl-3-benzylimidazolium chloride; 1,5-diazabicyclo(4.3.0)nonene cycloamidine compounds and derivatives thereof, such as diazabicycloalkenes such as 1,8-diazabicyclo(5.4.0)undecene-7 and its salts, tertiary amino group-containing compounds such as triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol, organic phosphine compounds such as triphenylphosphine, diphenyl(p-tolyl)phosphine, tris(alkylphenyl)phosphine, tris(alkoxyphenyl)phosphine, tris(alkyl alkoxyphenyl)phosphine, tris(dialkylphenyl)phosphine, tris(trialkylphenyl)phosphine, tris(tetraalkylphenyl)phosphine, tris(dialkoxyphenyl)phosphine, tris(trialkoxyphenyl)phosphine, tris(tetraalkoxyphenyl)phosphine, trialkylphosphine, dialkylarylphosphine, and alkyldiarylphosphine, and dicyandiazide.

[0136] These curing accelerators may be used alone or in combination of two or more.

[0137] Among these curing accelerators, taking into consideration both the curing acceleration effect and the electrical insulation performance of the cured product of the present embodiment described below, preferred curing accelerators are melamine, imidazole-based compounds, cycloamidine compounds and derivatives thereof, phosphine-based compounds and amine-based compounds, and more preferred are melamine, 1,5-diazabicyclo(4.3.0)nonene-5 and salts thereof, and 1,8-diazabicyclo(5.4.0)undecene-7 and salts thereof.

[0138] The amount of these curing accelerators is not particularly limited as long as the curing acceleration effect can be achieved. However, from the viewpoint of the curability of the curable composition according to this embodiment and the electrical insulation properties and water resistance of the cured product of this embodiment described later, it is preferable to mix the curing accelerator in the range of 0.05 to 5 parts by mass, and more preferably in the range of 0.1 to 3.0 parts by mass, relative to 100 parts by mass of the total amount of component a and component c. When the amount is in the range of 0.05 to 5 parts by mass, the curable composition according to this embodiment can be cured in a short time, and the electrical insulation properties and water resistance of the cured product obtained by curing the composition of this embodiment described later are good.

[0139] (Other Ingredients)

[0140] When the curable composition according to this embodiment is cured, a cured product having good electrical insulating properties is obtained, and therefore the composition can be used, for example, as a resist ink for insulating and protecting wiring.

[0141] Furthermore, to the curable composition according to this embodiment, surfactants such as a leveling agent, and known colorants such as phthalocyanine blue, phthalocyanine green, iodine green, disazo yellow, crystal violet, carbon black, and naphthalene black may be added, if necessary.

[0142] Furthermore, when it is necessary to suppress oxidative deterioration of component a and discoloration during heating, it is possible and preferable to add an antioxidant such as a phenol-based antioxidant, a phosphite-based antioxidant, or a thioether-based antioxidant.

[0143] If necessary, a flame retardant and a lubricant may also be added.

[0144] The curable composition according to the present embodiment can be obtained by uniformly kneading and mixing some or all of the components with a roll mill, a bead mill, etc. When some of the components are mixed, the remaining components can be mixed when actually using the composition.

[0145] (Viscosity of the curable composition according to this embodiment)

[0146] The curable composition according to the present embodiment has excellent handleability, while maintaining the physical properties such as the above-mentioned wire breakage suppression, low warpage, flexibility, and defoaming property at an excellent level. From such a viewpoint, the viscosity of the curable composition according to the present embodiment at 25°C can be preferably 10,000 to 100,000 mPa·s. The lower limit of the viscosity is more preferably 20,000 mPa·s or more, even more preferably 23,000 mPa·s or more, and even more preferably 25,000 mPa·s or more. The upper limit of the viscosity is more preferably 60,000 mPa·s or less, even more preferably 50,000 mPa·s or less, and even more preferably 45,000 mPa·s or less. In this specification, the viscosity of the curable composition according to this embodiment at 25°C is the viscosity measured using a cone / plate viscometer (manufactured by Brookfield, model: DV-II+Pro, spindle model number: CPE-52) at a rotation speed of 10 rpm, 7 minutes after the start of rotation.

[0147] (Thixotropy index of the curable composition according to this embodiment)

[0148] Furthermore, when the curable composition according to the present embodiment is used as a resist ink composition for insulating and protecting wiring (i.e., an overcoat agent for wiring boards) or the like, it is desirable to set the thixotropy index of the curable composition according to the present embodiment within a certain range in order to improve the printability of the composition.

[0149] The "thixotropy index" described in this specification is defined as the ratio of the viscosity at a rotation speed of 1 rpm at 25°C to the viscosity at a rotation speed of 10 rpm at 25°C (viscosity at 1 rpm / viscosity at 10 rpm), measured using a cone / plate viscometer (Brookfield, model: DV-III+Pro, spindle model number: CPE-52).

[0150] When the curable composition according to the present embodiment is used as an overcoat agent for wiring boards, in order to improve the printability of the curable composition according to the present embodiment, the thixotropy index of the composition is preferably 1.1 or more, more preferably in the range of 1.1 to 3.0, and even more preferably in the range of 1.1 to 2.5. When the curable composition according to the present embodiment is used as an overcoat agent for wiring boards, if the thixotropy index of the curable composition is 1.1 to 3.0, the composition can be made to have a constant film thickness after printing the curable composition, the printing pattern can be maintained, and the defoaming property of the printed film of the composition is also good.

[0151] <Cured product and overcoat film for flexible wiring boards>

[0152] The above-described curable composition can be cured and suitably used as a cured product. That is, the cured product according to the present embodiment is a cured product obtained by curing the above-described curable composition.

[0153] Such a cured product can be suitably used as an overcoat film for a flexible wiring board, etc. That is, the overcoat film for a flexible wiring board according to this embodiment is an overcoat film for a flexible wiring board that includes the above-mentioned cured product.

[0154] The cured product of the present embodiment and the overcoat film of the present embodiment can be obtained, for example, by heating the curable composition of the present embodiment and proceeding with the curing reaction. There is no particular limitation on the method for obtaining the cured product of the present embodiment as a cured film, but for example, the cured film or overcoat film can be obtained by going through the following steps. (First step) A step of printing the curable composition according to the present embodiment onto a substrate or the like to obtain a printed film. (Second step) A step of thermally curing the printed film obtained in the first step, or the printed film obtained in the first step by placing the printed film obtained in the first step in an atmosphere of 40°C to 100°C to evaporate a part or all of the solvent in the printed film, from which a part or all of the solvent has been removed, in an atmosphere of 100°C to 170°C to obtain a cured film or an overcoat film.

[0155] The printing method of the curable composition according to the present embodiment in the first step is not particularly limited. For example, the above-mentioned curable composition can be applied to a substrate or the like by a screen printing method, a roll coater method, a spray method, a curtain coater method, or the like to obtain a printed film.

[0156] The operation of evaporating the solvent in the second step is an operation that is performed as necessary, and the operation of thermal curing may be performed immediately after the operation of the first step, so that the curing reaction and removal of the solvent are performed together. When the operation of evaporating the solvent before thermal curing in the second step is performed, the temperature is usually 40° C. to 100° C., preferably 60° C. to 100° C., and more preferably 70° C. to 90° C., taking into consideration the evaporation rate of the solvent and the rapid transition to the thermal curing step. The time for evaporating the solvent in the second step is not particularly limited, but is preferably 10 minutes to 120 minutes, and more preferably 20 minutes to 100 minutes.

[0157] The temperature of the heat curing carried out in the second step is preferably in the range of 100° C. to 170° C., more preferably 105° C. to 160° C., and further preferably 110° C. to 150° C. The time of the heat curing carried out in the second step is not particularly limited, but is preferably in the range of 20 minutes to 240 minutes, and more preferably in the range of 30 minutes to 120 minutes.

[0158] <Flexible wiring board and method for manufacturing the flexible wiring board>

[0159] The flexible wiring board of the present embodiment and the manufacturing method of the flexible wiring board of the present embodiment will be described. The curable composition of the present embodiment can be used, for example, as a resist ink for insulating and protecting wiring, and the cured product of the present embodiment can be used as an insulating and protecting film. In particular, it can be used as a resist for insulating and protecting wiring by covering all or part of the wiring of a flexible wiring board such as a chip-on film.

[0160] The present embodiment is a flexible wiring board in which a part or the whole of the surface on which the wiring is formed of a flexible wiring board formed on a flexible substrate is covered with the cured product of the present embodiment (for example, the above-mentioned overcoat film for flexible wiring boards, etc.). In addition, the wiring covered with the cured product of the present embodiment is preferably a tin-plated copper wiring, taking into consideration the prevention of oxidation of the wiring and economical aspects.

[0161] The manufacturing method according to this embodiment is a method for manufacturing a flexible wiring board covered with a protective film, characterized in that the curable composition according to this embodiment is printed on at least a part of a wiring pattern portion of a flexible wiring board to form a printed film on the pattern, and the printed film is heat-cured at 100° C. to 170° C. to form a protective film. For example, the protective film for a flexible wiring board can be formed through the following steps A to C. (Step A) A step of printing the curable composition according to the present embodiment onto at least a part of a wiring pattern portion of a flexible wiring board to form a printed film on the pattern. (Step B) A step of evaporating a part or all of the solvent in the printed film by placing the printed film obtained in Step A in an atmosphere of 40°C to 100°C. (Step C) A step of curing the printed film obtained in step A or the printed film obtained in step B by heating at 100° C. to 170° C. to form a protective film for the flexible wiring board.

[0162] In this embodiment, more preferably, (Step A) A step of printing the curable composition according to the present embodiment on a part or the whole of a surface of a flexible wiring board having wiring formed on a flexible substrate, on which wiring is formed, to form a printed film on the wiring; (Step B) A step of evaporating a part or all of the solvent in the printed film by placing the printed film obtained in Step A in an atmosphere of 40°C to 100°C; (Step C) A step of curing the printed film obtained in step A or the printed film obtained in step B by heating at 100°C to 170°C to form an overcoat film. The method for producing a flexible wiring board covered with an overcoat film includes the steps of:

[0163] The operation of evaporating the solvent in step B is an operation that is performed as necessary, and the operation of thermal curing may be performed immediately after the operation of step A, so that the curing reaction and removal of the solvent are performed together. When the operation of evaporating the solvent is performed before thermal curing in step B, the temperature is usually 40° C. to 100° C., preferably 60° C. to 100° C., and more preferably 70° C. to 90° C., taking into consideration the evaporation rate of the solvent and a rapid transition to the thermal curing step. The time for evaporating the solvent in step B is not particularly limited, but is preferably 10 minutes to 120 minutes, and more preferably 20 minutes to 100 minutes.

[0164] The conditions for the thermal curing carried out in step C are in the range of 100° C. to 170° C. from the viewpoints of preventing diffusion of the plating layer and obtaining low warpage, flexibility, and softness, etc., suitable for a protective film. The thermal curing temperature is preferably 105° C. to 160° C., and more preferably 110° C. to 150° C. The time for the thermal curing carried out in step C is not particularly limited, but is preferably 10 minutes to 150 minutes, and more preferably 15 minutes to 120 minutes.

[0165] As described above, the curable composition according to the present embodiment, when cured to form a cured product, is excellent in breakage suppression, low warpage, flexibility, etc., and therefore when the curable composition according to the present embodiment is applied to a flexible substrate such as a flexible wiring board or a polyimide film and then a cured product (protective film) is produced by a curing reaction, the warpage of the flexible wiring board with the protective film or the flexible substrate with the protective film is small, and the alignment in the subsequent IC chip mounting process can be facilitated. Therefore, the curable composition according to the present embodiment can be suitably used to form an overcoat film for a flexible wiring board.

[0166] Furthermore, the curable composition according to the present embodiment is expected to provide good handleability, and when cured, it is expected to provide good adhesion to a substrate, flexibility, moisture resistance, and the like, as well as good long-term electrical insulation reliability.

[0167] Furthermore, the cured product of the present embodiment is expected to have at least excellent breakage prevention properties and good flexibility that contributes to this property, and is therefore suitable for providing a flexible wiring board with an electrically insulating protective film that is less susceptible to cracking (e.g., a flexible printed wiring board such as a COF). EXAMPLES

[0168] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0169] <Acid value measurement> The solvent in the polyurethane solution used in this embodiment was distilled off under reduced pressure while heating to obtain component a. The acid value of component a obtained by the above method was measured in accordance with the potentiometric titration method of JIS K0070. The apparatus used for the potentiometric titration is described below. Device name: Kyoto Electronics Manufacturing Co., Ltd. Automatic potentiometric titrator AT-510 Electrode: Kyoto Electronics Manufacturing Co., Ltd. composite glass electrode C-173

[0170] <Measurement of number average molecular weight of component a> The number average molecular weight is a polystyrene-equivalent number average molecular weight measured by GPC, and the GPC measurement conditions are as follows. Device name: JASCO Corporation HPLC unit HSS-2000 Column: Shodex column LF-804 Mobile phase: Tetrahydrofuran Flow rate: 1.0mL / min Detector: JASCO RI-2031Plus Temperature: 40.0℃ Sample volume: Sample loop 100μL Sample concentration: Adjusted to around 0.1% by mass

[0171] <Measurement of viscosity of solution containing component a>

[0172] The viscosity of the polyurethane solution was measured by the following method. Using approximately 0.8 g of the polyurethane solution, a cone / plate type viscometer (Brookfield, model: DV-II+Pro, spindle model number: CPE-52) was used to measure the viscosity 7 minutes after the start of the measurement at a temperature of 25.0°C and a rotation speed of 5 rpm.

[0173] <Measurement of Viscosity of Curable Composition>

[0174] The viscosity of the curable composition was measured by the following method. Using approximately 0.6 g of the curable composition, the viscosity was measured 7 minutes after the start of measurement using a cone / plate type viscometer (manufactured by Brookfield, model: DV-II+Pro, spindle model number: CPE-52) at a temperature of 25.0°C and a rotation speed of 10 rpm.

[0175] <Synthesis of polyester polyol>

[0176] (Reference synthesis example 1) In a reaction vessel equipped with a stirrer, a thermometer, and a condenser with a distillation apparatus, 983.5 g (6.74 mol) of phthalic anhydride and 879.2 g (7.44 mol) of 1,6-hexanediol were added, and the internal temperature of the reaction vessel was raised to 140°C using an oil bath, and stirring was continued for 4 hours. Then, while continuing stirring, 1.74 g of mono-n-butyltin oxide was added, and the internal temperature of the reaction vessel was gradually raised, and a vacuum pump was connected to gradually reduce the pressure in the reaction vessel, and water was removed by distillation under reduced pressure outside the reaction vessel. Finally, the internal temperature was raised to 220°C, and the pressure was reduced to 133.32 Pa. After 15 hours, it was confirmed that water was no longer completely distilled off, and the reaction was terminated. The hydroxyl value of the obtained polyester polyol (hereinafter referred to as polyester diol (α)) was measured, and the hydroxyl value was 53.1 mg-KOH / g.

[0177] <Synthesis of Polyurethane>

[0178] (Example 1 of Synthesis)

[0179] A reaction vessel equipped with a stirrer, a thermometer, and a condenser was charged with 10.7 g (24.4 mmol, aromatic ring 97.6 mmol) of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (manufactured by Osaka Gas Chemicals Co., Ltd., trade name: BPEF), 61.52 g of P-2030 (manufactured by Kuraray Co., Ltd., polyester polyol composed of isophthalic acid / 3-methyl-1,5-pentanediol), 6.48 g of 2,2-dimethylolpropionic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) as a carboxyl group-containing diol, and 137.7 g of γ-butyrolactone as a solvent, and the mixture was heated to 100° C. to dissolve all of the raw materials.

[0180] The temperature of the reaction liquid was lowered to 90°C, and 28.31g of methylene bis(4-cyclohexyl isocyanate) (manufactured by Sumika Bayer Urethane Co., Ltd., trade name: Desmodur-W) was dropped over 30 minutes using a dropping funnel. The reaction was carried out at 145°C to 150°C for 8 hours, and after confirming by IR that the absorption due to the C=O stretching vibration of the isocyanato group was almost no longer observed, 1.5g of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) and 24.3g of diethylene glycol diethyl ether (manufactured by Nippon Nyukazai Co., Ltd.) were dropped, and the reaction was further carried out at 80°C for 3 hours to obtain a solution containing polyurethane having a carboxyl group and an aromatic ring concentration of 3.1mmol / g (hereinafter referred to as "polyurethane solution A1").

[0181] The viscosity of the obtained polyurethane solution A1 was 120,000 mPa s. The polyurethane (hereinafter referred to as "polyurethane AU1") contained in the polyurethane solution A1 had a number average molecular weight of 20,000 and an acid value of 25.0 mg-KOH / g, and the polyurethane had a carboxyl group and an aromatic ring concentration of 3.1 mmol / g (hereinafter referred to as "polyurethane AU1").

[0182] The solid content concentration in the polyurethane solution A1 was 40.0% by mass.

[0183] (Example 2 of Synthesis)

[0184] A reaction vessel equipped with a stirrer, a thermometer, and a condenser was charged with 21.0 g of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (manufactured by Osaka Gas Chemicals Co., Ltd., product name: BPEF), 66.7 g of the above polyester diol (α) (polyester polyol composed of phthalic acid / 1,6-hexanediol), 3.00 g of 2,2-dimethylolpropionic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) as a carboxyl group-containing diol, and 83.24 g of γ-butyrolactone as a solvent, and heated to 100° C. to dissolve all of the raw materials.

[0185] The temperature of the reaction solution was lowered to 90 ° C., and a solution of 26.50 g of diphenylmethane-4,4'-diisocyanate (manufactured by Tosoh Corporation, trade name: Millionate MT) dissolved in 60.0 g of γ-butyrolactone was dropped over 20 minutes using a dropping funnel. The reaction was carried out at 125 ° C. to 130 ° C. for 8 hours, and after confirming by IR that the absorption due to the C = O stretching vibration of the isocyanato group was almost no longer observed, 1.5 g of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.), 6.19 g of γ-butyrolactone, and 26.37 g of diethylene glycol diethyl ether (manufactured by Nippon Nyukazai Co., Ltd.) were dropped, and the reaction was further carried out at 80 ° C. for 3 hours to obtain a solution containing polyurethane having a carboxyl group and an aromatic ring concentration of 5.6 mmol / g (hereinafter referred to as "polyurethane solution A2").

[0186] The viscosity of the obtained polyurethane solution A2 was 120,000 mPa s. The polyurethane contained in the polyurethane solution A2 (hereinafter referred to as "polyurethane AU2") having a carboxyl group and an aromatic ring concentration of 5.6 mmol / g had a number average molecular weight of 20,000 and an acid value of 10.6 mg-KOH / g.

[0187] The solid content concentration in the polyurethane solution A2 was 40.0% by mass.

[0188] (Example 3 of Synthesis)

[0189] A reaction vessel equipped with a stirrer, a thermometer, and a condenser was charged with 5.0 g of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (manufactured by Osaka Gas Chemicals Co., Ltd., product name: BPEF), 73.00 g of polycarbonate diol (polyester polyol consisting of 3-methyl-1,5-pentanediol / 1,6-hexanediol, product name: Kuraray Polyol C-2090, hydroxyl value: 1955), 6.75 g of 2,2-dimethylolpropionic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) as a carboxyl group-containing diol, and 136.34 g of γ-butyrolactone as a solvent, and the mixture was heated to 100° C. to dissolve all of the raw materials.

[0190] The temperature of the reaction liquid was lowered to 90°C, and 26.80g of methylene bis(4-cyclohexyl isocyanate) (manufactured by Sumika Bayer Urethane Co., Ltd., product name: Desmodur-W) was dropped over 30 minutes using a dropping funnel. The reaction was carried out at 145°C to 150°C for 10 hours, and after confirming by IR that the absorption due to the C=O stretching vibration of the isocyanato group was almost no longer observed, 1.5g of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.), 5.89g of γ-butyrolactone, and 25.10g of diethylene glycol diethyl ether (manufactured by Nippon Nyukazai Co., Ltd.) were dropped, and the reaction was further carried out at 80°C for 3 hours to obtain a solution containing polyurethane having a carboxyl group and an aromatic ring concentration of 0.4mmol / g (hereinafter referred to as "polyurethane solution A3").

[0191] The viscosity of the obtained polyurethane solution A3 was 120,000 mPa s. The polyurethane contained in the polyurethane solution A3, which had a carboxyl group and an aromatic ring concentration of 0.4 mmol / g (hereinafter referred to as "polyurethane AU3"), had a number average molecular weight of 20,000 and an acid value of 25.0 mg-KOH / g.

[0192] The solid content concentration in the polyurethane solution A3 was 40.0% by mass.

[0193] (Comparative Synthesis Example 1)

[0194] A reaction vessel equipped with a stirrer, a thermometer, and a condenser was charged with 248.0 g of C-1090 (manufactured by Kuraray Co., Ltd., a (poly)carbonate diol made from 1,6-hexanediol and 3-methyl-1,5-pentanediol as raw materials, with a hydroxyl value of 122.22 mg-KOH / g) as a (poly)carbonate polyol, 47.5 g of 2,2-dimethylolbutanoic acid (manufactured by Nippon Kasei Co., Ltd.) as a carboxyl group-containing diol, 2.7 g of trimethylolethane (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a polyol other than the (poly)carbonate polyol and the carboxyl group-containing diol, 467.5 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Co., Ltd.) and 82.5 g of diethylene glycol diethyl ether (manufactured by Nippon Nyukazai Co., Ltd.) as a solvent, and the mixture was heated to 100° C. to dissolve all of the raw materials.

[0195] The temperature of the reaction liquid was lowered to 90° C., and 150.4 g of methylenebis(4-cyclohexylisocyanate) (manufactured by Sumika Bayer Urethane Co., Ltd., trade name: Desmodur-W) as a diisocyanate compound was added dropwise using a dropping funnel over 30 minutes.

[0196] The reaction was carried out at 120°C for 8 hours, and it was confirmed by IR that the absorption due to the C=O stretching vibration of the isocyanato group was almost no longer observed. Then, 1.5 g of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) was dropped into the reaction solution, and the reaction was further carried out at 80°C for 3 hours to obtain a polyurethane solution having a carboxyl group and a carbonate bond (hereinafter referred to as "polyurethane solution B1").

[0197] The viscosity of the obtained polyurethane solution B1 was 145,000 mPa·s. The number average molecular weight of the polyurethane (hereinafter referred to as "polyurethane BU1") having an aromatic ring concentration of 0 mmol / g contained in the obtained polyurethane solution B1 was 14,000, and the acid value of polyurethane BU1 was 40.0 mg-KOH / g. The solid content concentration in polyurethane solution B1 was 45.0 mass%.

[0198] (Comparative Synthesis Example 2)

[0199] In a 1-liter three-neck flask equipped with a distillation apparatus, 611.0 g of bis[4-(2-hydroxyethoxy)phenyl]methane, 297.3 g of dimethyl isophthalate, and 0.5 g of dioctyltin oxide were charged and heated at 180°C under a nitrogen stream to distill off the resulting methanol. When about 50 g of methanol was distilled off, the pressure in the reaction system was reduced to 1.3 kPa to increase the distillation rate of methanol. After the theoretical amount of methanol was distilled off, the system was heated for another hour and held at 185°C-0.13 kPa for one hour, after which the reactor was cooled to obtain 810 g of polyester polyol (hereinafter referred to as polyester diol (β)). The hydroxyl value of the obtained polyester diol (β) was measured and found to be 55.4 mg-KOH / g.

[0200] A reaction vessel equipped with a stirrer, a thermometer, and a condenser was charged with 11.0 g of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (manufactured by Osaka Gas Chemicals Co., Ltd., product name: BPEF), 61.52 g of polyester diol (β), 6.32 g of 2,2-dimethylolpropionic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) as a carboxyl group-containing diol, and 135.6 g of γ-butyrolactone as a solvent, and the mixture was heated to 100° C. to dissolve all of the raw materials.

[0201] The temperature of the reaction liquid was lowered to 90°C, and 27.00g of diphenylmethane-4,4'-diisocyanate (manufactured by Sumika Bayer Urethane Co., Ltd., product name: MDI) was added as a polyisocyanate compound in several portions over 30 minutes using a dropping funnel. The reaction was carried out at 145°C to 150°C for 15 hours, and after confirming by IR that the absorption due to the C=O stretching vibration of the isocyanato group was almost no longer observed, 1.5g of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) and 23.9g of diethylene glycol diethyl ether (manufactured by Nippon Nyukazai Co., Ltd.) were dropped, and the reaction was further carried out at 80°C for 3 hours to obtain a solution containing polyurethane having a carboxyl group and an aromatic ring concentration of 6.9mmol / g (hereinafter referred to as "polyurethane solution B2").

[0202] The viscosity of the obtained polyurethane solution B2 was 125,000 mPa s. The polyurethane (hereinafter referred to as "polyurethane BU2") contained in the polyurethane solution B2 had a carboxyl group and an aromatic ring concentration of 6.9 mmol / g and had a number average molecular weight of 20,000, and the acid value of the polyurethane BU2 was 25.0 mg-KOH / g.

[0203] The solid content concentration in the polyurethane solution B2 was 40.0% by mass.

[0204] The properties of the polyurethanes AU1 to AU3 and the polyurethanes BU1 and BU2 are shown in Table 1.

[0205] [Table 1]

[0206] <Production of base compound>

[0207] (Example Mixture 1)

[0208] 160.0 parts by mass of polyurethane solution A1, 6.3 parts by mass of silica powder (manufactured by Nippon Aerosil Co., Ltd., product name: Aerosil R-974), 0.72 parts by mass of melamine (manufactured by Nissan Chemical Industries, Ltd.) as a curing accelerator, and 8.4 parts by mass of diethylene glycol diethyl ether were mixed, and the silica powder and curing accelerator were mixed into polyurethane solution A1 using a three-roll mill (manufactured by Inoue Seisakusho Co., Ltd., model: S-4 3 / 4 x 11). Then, 2.0 parts by mass of a defoamer (olefin-based defoamer containing polyolefin, manufactured by BYK Japan Co., Ltd., product name: BYK-1791) were added and mixed using a spatula. This mixture was designated as main compound mixture C1.

[0209] (Example Mixture 2)

[0210] 160.0 parts by mass of polyurethane solution A1, 6.3 parts by mass of silica powder (manufactured by Nippon Aerosil Co., Ltd., product name: Aerosil R-974), 1.0 parts by mass of hydrotalcite (manufactured by Kyowa Chemical Industry Co., Ltd., product name: DHT-4A), 0.72 parts by mass of melamine (manufactured by Nissan Chemical Industries Co., Ltd.) as a curing accelerator, and 8.4 parts by mass of diethylene glycol diethyl ether were mixed, and the silica powder and curing accelerator were mixed into polyurethane solution A1 using a three-roll mill (manufactured by Inoue Seisakusho Co., Ltd., model: S-4 3 / 4 x 11). Then, 2.0 parts by mass of a defoamer (olefin-based defoamer containing polyolefin, manufactured by BYK Japan Co., Ltd., product name: BYK-1791) were added and mixed using a spatula. This mixture was designated as main compound mixture C2.

[0211] (Examples 3 to 7)

[0212] The mixtures were blended according to the blending compositions shown in Table 2 in the same manner as in Blending Example 1. The blends prepared in Blending Examples 3 to 7 were designated as Main Blends C3 to C7, respectively. The numerical values ​​in the table indicate "parts by mass." "Disparlon 230HF" is an acrylic defoamer containing an acrylic resin, and "TSA750S" is a silicone defoamer containing a silicone resin.

[0213] (Comparative formulation example 1)

[0214] 140.0 parts by mass of polyurethane solution B1, 5.5 parts by mass of silica powder (manufactured by Nippon Aerosil Co., Ltd., product name: Aerosil R-974), 0.72 parts by mass of melamine (manufactured by Nissan Chemical Industries, Ltd.) as a curing accelerator, and 8.4 parts by mass of diethylene glycol diethyl ether were mixed, and the silica powder and the curing accelerator were mixed into the polyurethane solution B1 using a three-roll mill (manufactured by Inoue Seisakusho Co., Ltd., model: S-4 3 / 4 x 11). Then, 2.0 parts by mass of a defoamer (olefin-based defoamer containing polyolefin, manufactured by BYK Japan Co., Ltd., product name: BYK-1791) were added and mixed using a spatula. This mixture was designated as the main compound mixture D1.

[0215] (Comparative formulation example 2)

[0216] The mixture was blended according to the composition shown in Table 2 in the same manner as in Example Blend 1. The mixture prepared in Comparative Blend 2 was designated as Base Blend D2. The values ​​in the table indicate parts by mass.

[0217] (Comparative formulation example 3)

[0218] The mixture was blended according to the composition shown in Table 2 in the same manner as in Blend Example 1. The blend prepared in Comparative Blend Example 3 was designated as Base Blend D3. The values ​​in the table indicate parts by mass.

[0219] [Table 2]

[0220] <Preparation of hardener solution>

[0221] (Example 1 of hardener solution formulation)

[0222] To a vessel equipped with a stirrer, a thermometer, and a condenser were added 16.85 parts by mass of an epoxy resin having the structure of the following formula (6) (manufactured by Mitsubishi Chemical Corporation, grade name: jER (registered trademark) 604, epoxy equivalent 120 g / eqv) and 18.25 parts by mass of diethylene glycol diethyl ether, and stirring was started.

[0223] While continuing the stirring, the temperature inside the container was raised to 40°C using an oil bath. After the internal temperature was raised to 40°C, stirring was continued for 30 minutes. After that, it was confirmed that jER (registered trademark) 604 was completely dissolved, and the solution was cooled to room temperature to obtain a solution containing jER (registered trademark) 604 at a concentration of 48% by mass. This solution is referred to as hardener solution E1.

[0224] [ka]

[0225] (Example 2 of hardener solution)

[0226] To a vessel equipped with a stirrer, a thermometer, and a condenser were added 16.85 parts by mass of an epoxy resin mainly composed of N,N-diglycidyl-4-(glycidyloxy)aniline (manufactured by Mitsubishi Chemical Corporation, grade name: jER (registered trademark) 630, epoxy equivalent 98 g / eqv) and 18.25 parts by mass of diethylene glycol diethyl ether, and stirring was started.

[0227] While continuing the stirring, the temperature inside the container was raised to 40°C using an oil bath. After the internal temperature was raised to 40°C, stirring was continued for 30 minutes. After that, it was confirmed that jER (registered trademark) 630 was completely dissolved, and the solution was cooled to room temperature to obtain a jER (registered trademark) 630-containing solution with a concentration of 48% by mass. This solution was designated as hardener solution E2.

[0228] <Mixing the base compound and the solution containing the hardener>

[0229] (Formulation example 1 of curable composition)

[0230] 88.7 parts by mass of the main compound C1 and 3.5 parts by mass of the curing agent solution E1 were placed in a plastic container. Furthermore, in order to match the viscosity with the curable compositions of other compounding examples and comparative compounding examples described later, 3.0 parts by mass of diethylene glycol diethyl ether and 1.5 parts by mass of diethylene glycol monoethyl ether acetate were added as solvents. Mixing was performed by stirring with a spatula at room temperature for 5 minutes to obtain a curable composition (hereinafter referred to as "curable composition F1").

[0231] (Formulation Examples 2 to 8 of Curable Composition)

[0232] They were blended according to the blending compositions shown in Table 3 in the same manner as in Formulation Example 1 of the curable composition. The blends prepared in Formulation Examples 2 to 8 of the curable composition were named curable compositions F2 to F8, respectively.

[0233] (Comparative Formulation Example 1 of Curable Composition)

[0234] 78.6 parts by mass of the base compound D1 and 5.6 parts by mass of the curing agent solution E1 were placed in a plastic container. Furthermore, in order to match the viscosity with the curable compositions of other compounding examples and comparative compounding examples, 4.8 parts by mass of diethylene glycol diethyl ether and 1.3 parts by mass of diethylene glycol monoethyl ether acetate were added as solvents. Mixing was performed by stirring with a spatula at room temperature for 5 minutes to obtain a curable composition (hereinafter referred to as "curable composition G1").

[0235] (Comparative Formulation Example 2 of Curable Composition)

[0236] A curable composition (hereinafter, referred to as "curable composition G2") was obtained by preparing the composition shown in Table 3 in the same manner as in the above-mentioned "Comparative Formulation Example 1 of Curable Composition".

[0237] A curable composition (hereinafter, referred to as "curable composition G3") was obtained by preparing the composition shown in Table 3 in the same manner as in the above-mentioned "Comparative Formulation Example 1 of Curable Composition".

[0238] The blending composition with the polyurethane solution for each of the base blends of the curable compositions F1 to F8 and the curable compositions G1 to G3 is shown in Table 3. In addition, the blending compositions of each component of the curable compositions F1 to F8 and the curable compositions G1 to G3 are summarized in Table 4.

[0239] In Table 4, "a / (a+c)" represents the content (mass%) of component a relative to the total amount of components a and c. In Table 4, "b / (a+b+c)" represents the content (mass%) of component b relative to the total amount of components a, b, and c. In Table 4, "(d+e)" represents the total amount (mass %) of component d and component e in the curable composition. In Table 4, "(d+e) / (total amount of composition-b)" represents the total amount of component d and component e when the sum of the components obtained by excluding the content of component b from the total amount of the curable composition is taken as 100 parts by mass. In Table 4, "e / d" represents the content ratio (mass%) of component e to component d.

[0240] [Table 3]

[0241] [Table 4]

[0242] (Examples 1 to 8, Comparative Examples 1 to 3)

[0243] Curable compositions F1 to F8 and curable compositions G1 to G3 were used to evaluate breakage prevention properties, warpage properties, flexibility, and defoaming time by the methods described below. The results are shown in Table 5.

[0244] <Evaluation of the disconnection prevention properties of wiring on printed circuit boards (MIT test)>

[0245] A flexible wiring board was produced by etching a flexible copper-clad laminate (manufactured by Sumitomo Metal Mining Co., Ltd., grade name: Esperflex US, copper thickness: 8 μm, polyimide thickness: 38 μm), and the substrate (copper wiring width / copper wiring interval=15 μm / 15 μm) with a fine comb pattern described in JPCA-ET01 was tin-plated. The curable composition F1 was applied by screen printing so that the thickness of the printed film from the wiring surface was 5 μm (after drying). The printed film-formed wiring board obtained was placed in a hot air circulation dryer at 80 ° C for 30 minutes, and then placed in a hot air circulation dryer at 120 ° C for 120 minutes to cure the printed film.

[0246] Using this test piece, tests were carried out under the following conditions according to the method described in JIS C-5016. (Test conditions) Testing machine: Tester Sangyo Co., Ltd. MIT Tester BE202 Bending speed: 10 times / min Load: 200g Bending angle: ±90° Grip tip radius: 0.5 mm Under the above test conditions, the number of times of bending was increased by 10 times each, and the presence or absence of cracks in the wiring was visually observed, and the number of times of bending when cracks occurred was recorded. The results are shown in Table 5. The same evaluations were carried out using curable compositions F2 to F8 and curable compositions G1 to G3. The results are also shown in Table 5.

[0247] <Evaluation of warpage>

[0248] The curable composition F1 was applied to a substrate by screen printing using a #180 mesh polyester plate, and the substrate was placed in a hot air circulation dryer at 80° C. for 30 minutes. The substrate was then placed in a hot air circulation dryer at 120° C. for 60 minutes to cure the applied curable composition F1. A 25 μm thick polyimide film (Kapton (registered trademark) 100EN, manufactured by DuPont-Toray Co., Ltd.) was used as the substrate.

[0249] The curable composition was applied, and the cured film was cured using a hot air circulation dryer. The film was cut into a diameter of 50 mm using a circle cutter. The film cut into a circle exhibited deformation in the form of a convex or concave warp near the center. The substrate on which the cured film was formed, cut with the circle cutter, was left standing in a downward convex state after 1 hour, i.e., the center of the substrate on which the cured film was formed was in contact with a horizontal surface, and the maximum and minimum values ​​of the warp height from the horizontal surface were measured and the average value was calculated. The sign indicates the direction of warp, and when left standing in a downward convex state, the cured film was on the upper side of the copper substrate or polyimide film, which was marked as "+", and the cured film was on the lower side, which was marked as "-". If the warp was less than +3.0 mm, the specimen was deemed to have passed the test. The results are shown in Table 5.

[0250] The same evaluation was carried out using curable compositions F2 to F8 and curable compositions G1 to G3. The results are also shown in Table 5.

[0251] <Flexibility evaluation>

[0252] On the copper of a flexible copper-clad laminate (manufactured by Sumitomo Metal Mining Co., Ltd., grade name: Esperflex, copper thickness: 8 μm, polyimide thickness: 38 μm), the curable composition F1 was applied by screen printing so as to have a size of 75 mm wide, 110 mm long, and a film thickness of 15 μm after curing, and then held at room temperature for 10 minutes and cured by placing in a hot air circulation dryer at 120 ° C for 60 minutes. The PET film backing of the prepared test piece was peeled off, cut into a strip of 10 mm wide with a cutter knife, folded about 180 degrees so that the cured film surface was on the outside, and compressed for 3 seconds at 0.5 ± 0.2 MPa using a compressor. The bent part was observed under a 30x microscope in the bent state to confirm the presence or absence of cracks.

[0253] The curable compositions F1 to F8 were evaluated for flexibility, and all of them were found to have "no cracks." On the other hand, the curable compositions G1 to G3 were evaluated for flexibility, and while G1 and G3 were found to have "no cracks," G2 was found to have "cracks."

[0254] <Defoaming time>

[0255] The curable composition F1 was applied by screen printing onto the copper of a flexible copper-clad laminate (manufactured by Sumitomo Metal Mining Co., Ltd., grade name: Esperflex, copper thickness: 8 μm, polyimide thickness: 38 μm) so as to have a width of 75 mm, a length of 110 mm, and a film thickness of 15 μm after curing. At this time, bubbles on the coating surface were visually observed, and the time until the bubbles disappeared was measured, taking the time from the completion of the screen printing as 0 seconds, and was taken as the defoaming time.

[0256] The same evaluation was carried out using curable compositions F2 to F8 and curable compositions G1 to G3. The results are also shown in Table 5.

[0257] [Table 5]

[0258] From the above results, it was at least confirmed that the curable composition of this example is excellent in at least breakage prevention properties, low warpage properties, flexibility, and defoaming properties, and that the cured product is useful as an insulating protective film for flexible wiring boards, etc.

Claims

1. (Component a) a polyurethane having a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol / g, the polyurethane containing an organic residue derived from a polyisocyanate; (Component b) a solvent, (Component c) a compound having two or more epoxy groups in one molecule, and (Component d) a first antifoam agent containing an olefin; and wherein the curable composition does not contain fluorine atoms.

2. Component a is represented by formula (1) 【Chemistry 1】 2. The curable composition according to claim 1, which is a polyurethane having a structural unit represented by the formula:

3. Component a is represented by formula (2) 【Chemistry 2】 (Here, R 1 each independently represents a phenylene group or a phenylene group having a substituent. The curable composition according to claim 1 or 2, which is a polyurethane having a structural unit represented by the formula:

4. Component a is represented by formula (3) 【Chemistry 3】 (where n R 1 each independently represents a phenylene group or a phenylene group having a substituent, and (n+1) R 2 each independently represents an alkylene group having 3 to 9 carbon atoms, and n is a natural number of 50 or less. The curable composition according to claim 1 or 2, which is a polyurethane having a structural unit represented by the formula:

5. 3. The curable composition according to claim 1, wherein in component a, the organic residue derived from a cyclic aliphatic polyisocyanate accounts for 70 mol % or more of the total amount of organic residues derived from the polyisocyanate.

6. The curable composition according to claim 1 or 2, wherein the component a is 60 to 99.9 mass% based on the total amount of the components a and c.

7. The curable composition according to claim 1 or 2, wherein the component b is 25 to 75 mass % based on the total amount of the components a, b and c.

8. 3. The curable composition according to claim 1, wherein the number average molecular weight of component a is 3,000 to 50,000 and the acid value of component a is 10 to 70 mgKOH / g.

9. The curable composition according to claim 1 or 2, further comprising (component e) a second defoamer containing an acrylic resin and / or a methacrylic resin.

10. The curable composition according to claim 9, wherein the total amount of component d and component e is 0.01 to 3 mass%.

11. The curable composition according to claim 9, wherein the total amount of components d and e is 0.01 to 5 mass% when the total amount of components obtained by excluding the content of component b from the total amount of the curable composition is taken as 100 mass%.

12. The curable composition according to claim 9, wherein component e is 1 to 150% by mass relative to component d.

13. The curable composition according to claim 1 or 2, further comprising (component f) at least one type of fine particles selected from the group consisting of inorganic fine particles and organic fine particles.

14. The curable composition of claim 13, wherein component f comprises silica microparticles.

15. The curable composition of claim 13, wherein component f comprises fine hydrotalcite particles.

16. A cured product of the curable composition according to claim 1 or 2.

17. An overcoat film for flexible wiring boards, comprising the cured product according to claim 16 .

18. 20. A flexible wiring board comprising wiring formed on a flexible substrate, the surface on which the wiring is formed being partly or entirely covered with the overcoat film for flexible wiring boards according to claim 17.

19. (Step A) a step of printing the curable composition according to claim 1 or 2 on a part or all of a surface of a flexible wiring board having wiring formed on a flexible substrate, thereby forming a printed film on the wiring; (Step B) A step of evaporating a part or all of the solvent in the printed film by placing the printed film obtained in Step A under an atmosphere of 40° C. to 100° C.; (Step C) A step of curing the printed film obtained in step A or the printed film obtained in step B by heating at 100° C. to 170° C. to form an overcoat film. The method for producing a flexible wiring board covered with an overcoat film includes the steps of:

Citation Information

Patent Citations

  • Production method of thermosetting resin composition and use of the same

    JP2017206591A

  • Defoaming agent

    JP2018118207A

  • Curable composition, cured object, overcoat film, coated flexible wiring board, and process for producing same

    WO2017110326A1

  • Method for producing flexible printed boards

    WO2022202082A1

  • Curable polyurethane composition

    JP1993247161A